2013
DOI: 10.1002/ffj.3176
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged anxiolytic‐like activity of sandalwood (Santalum album L.) oil in stress‐loaded mice

Abstract: The fragrance of Santalum album L. (sandalwood) has been used as a sedative. However, few reports have investigated the anxiolytic activity of sandalwood fragrance. Therefore, in this study, we examined the anxiolytic-like activity of hexane-extracted sandalwood oil (SAO). Male ICR mice, aged 5 weeks at the start of each experiment, were used. To mimic its clinical use, the effect of SAO after stress loading was investigated. Mice were individually housed in cages for 1 week and subjected to loaded water-immer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 25 publications
(36 reference statements)
0
16
0
Order By: Relevance
“…Okugawa et al additionally reported that after an intraperitoneal administration, α‐santalol was a strong antagonist of the dopamine D 2 and serotonin 5‐HT 2A receptor binding, although it was less potent than chlorpromazine when used as an antipsychotic agent (Okugawa et al ., ). We further reported that sandalwood oil, for which α‐santalol and β‐santalol are the main components, exhibited a prolonged anxiolytic‐like activity after inhaled administration in mice exposed to water‐immersion stress for 24 h (Satou et al ., ). Our findings suggested that after the inhaled administration, the volatile components produced these anxiolytic effects by neurological and pharmacological transfers.…”
Section: Introductionmentioning
confidence: 97%
“…Okugawa et al additionally reported that after an intraperitoneal administration, α‐santalol was a strong antagonist of the dopamine D 2 and serotonin 5‐HT 2A receptor binding, although it was less potent than chlorpromazine when used as an antipsychotic agent (Okugawa et al ., ). We further reported that sandalwood oil, for which α‐santalol and β‐santalol are the main components, exhibited a prolonged anxiolytic‐like activity after inhaled administration in mice exposed to water‐immersion stress for 24 h (Satou et al ., ). Our findings suggested that after the inhaled administration, the volatile components produced these anxiolytic effects by neurological and pharmacological transfers.…”
Section: Introductionmentioning
confidence: 97%
“…[1][2][3][4][5][6] We recently found that in vivo transferability by inhalation administration varies depending on the type of volatile compounds. It has been reported that essential oils of coniferous trees, juniper, lavender and sandalwood have anxiolytic-like activities, and the chemical components exhibiting these effects are reported to be linalool, linalyl acetate, a-pinene and a-santalo.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that essential oils of coniferous trees, juniper, lavender and sandalwood have anxiolytic-like activities, and the chemical components exhibiting these effects are reported to be linalool, linalyl acetate, a-pinene and a-santalo. [1][2][3][4][5][6] We recently found that in vivo transferability by inhalation administration varies depending on the type of volatile compounds. 7 For example, 1,8-cineole is not readily metabolized from within the brain, even at 30 min after inhalation.…”
Section: Introductionmentioning
confidence: 99%
“…Sandalwood oil is the volatile substance obtained through steam distillation of the heartwood of S. album and is widely used in aromatherapy and traditional medicine. [1][2][3][4] S. album contains a variety of aromatic compounds 5) and sesquiterpenes, [6][7][8] of which α-santalol is a major volatile compound that possesses various biological activities. [9][10][11] However, β-santalol, another major volatile sesquiterpene from S. album with the same bicyclo[2.2.1] heptane skeleton, shows few biological activities, including anti-Helicobacter pylori 12) and antiviral effects.…”
mentioning
confidence: 99%
“…These results prompted us to investigate the heartwood of S. album further. In this study, we isolated a rare type of sesquiterpene with a spiro bicyclic system (1), and seven new (2)(3)(4)(5)(6)(7)(8) and four known (9-12) β-santalol derivatives. The structures of these new β-santalol derivatives were determined by analysis of extensive spectroscopic data, including two-dimensional NMR data.…”
mentioning
confidence: 99%